Case report: Response to endocrine therapy in triple-negative breast cancer metastases with altered hormone receptors - Qin, Ruoyan; Qian, Jie; Shan, Mengjun; Ruan, Guangxin; Yang, Xiaofeng; Wang, Yanwen; Liu, Lingshuang (Frontiers in Oncology, 2023)
Triple-negative breast cancer refers to breast cancer patients with negative estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor (HER2). Metastatic triple-negative breast cancer is predominantly treated with chemotherapy, but later-line treatment remains challenging. Breast cancer is highly heterogeneous, and the expression of hormone receptors is often inconsistent between primary and metastatic lesions. Here, we report a case of triple-negative breast cancer 17 years after surgery with lung metastases for 5 years that progressed to pleural metastases after multiple lines of chemotherapy. The pleural pathology suggested ER (+) and PR (+) and transformation to luminal A breast cancer. This patient received fifth-line letrozole endocrine therapy and achieved partial response (PR). The patient's cough and chest tightness improved after treatment, associated tumor markers decreased, and progression-free survival (PFS) exceeded 10 months. Our results may be of clinical relevance for patients with hormone receptor alterations in advanced triple-negative breast cancer and suggest that individualized regimens should be developed for breast cancer based on the molecular expression of tumor tissue at the primary and metastatic sites.